Pengaruh Pendekatan Pembelajaran Bermain Terhadap Passing Bawah Permainan Bola Voli Siswa Kelas V SD Negeri Karangsari - Handikasari, Sherly Putri; Fauzan, Elang (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low level of underhand passing skills in volleyball among fifth-grade students at Karangsari Public Elementary School. Many students still make technical errors, resulting in their skills falling below the minimum passing criteria (KKM). This study aims to determine the effect of a play-based learning approach on students' underhand passing skills in volleyball. The research method used was an experiment with a quantitative approach. The research subjects consisted of 21 students. The data collection technique used a passing skill test administered before (pre-test) and after (post-test) the application of learning through play in Physical Education, Sports, and Health lessons. The research instrument was a passing skill test. Data analysis was performed through normality and homogeneity tests, followed by a t-test. The results show that the t-value of 12.429 is greater than the t-table value of 2.09 with a significance value of 0.000 < 0.05. This proves that there is a significant difference between the pretest and posttest scores. The average pretest score of students was 12.05, increasing to 19.80 on the posttest, with an average difference of 7.75 or an increase of 38.75%. Thus, it can be concluded that the play-based learning approach has a positive and significant effect on the underhand passing skills of fifth-grade students at Karangsari Public Elementary School.